Building a new platform to support public health emergency response in Africa: the AFENET Corps of Disease Detectives, 2018–2019 - Peter Nsubuga; Patrick M Nguku; Ben Masiira; Simon N Antara; Herbert B Kazoora; Olivia Namusisi; Notion T Gombe; Alain N Magazani; Ditu Kazambu; Sheba N Gitta; Christine Kihembo; Bernard Sawadogo; et al. (BMJ Global Health)
Public health emergency (PHE) response in sub-Saharan Africa is constrained by inadequate skilled public health workforce and underfunding. Since 2005, the African Field Epidemiology Network (AFENET) has been supporting field epidemiology capacity development and innovative strategies are required to use this workforce. In 2018, AFENET launched a continental rapid response team: the AFENET Corps of Disease Detectives (ACoDD). ACoDD comprises field epidemiology graduates and residents and was established to support PHE response. Since 2018, AFENET has deployed the ACoDD to support response to several PHEs. The main challenges faced during ACoDD deployments were financing of operations, ACoDD safety and security, resistance to interventions and distrust of the responders by some communities. Our experience during these deployments showed that it was feasible to mobilise and deploy ACoDD within 48 hours. However, the sustainability of deployments will depend on establishing strong linkages with the employers of ACoDD members. PHEs are effectively controlled when there is a fast deployment and strong linkages between the stakeholders. There are ongoing efforts to strengthen PHE preparedness and response in sub-Saharan Africa. ACoDD members are a competent workforce that can effectively augment PHE response. ACoDD teams mentored front-line health workers and community health workers who are critical in PHE response. Public health emergence response in sub-Saharan Africa is constrained by inadequacies in a skilled workforce and underfunding. ACoDD can be utilised to overcome the challenges of accessing a skilled public health workforce. To improve health security in sub-Saharan Africa, more financing of PHE response is needed.